Pre-treatment and Suitable Reagent Enabled a Reliable and Consistent for Molecular Detection of Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc4) - Listya Utami Karmawan; Fenny Martha Dwivany; Rizkita Rachmi Esyanti; I Nyoman Pugeg Aryantha (HAYATI Journal of Biosciences, 2019)
Fusarium wilt which is caused by the soil-borne fungus, Fusarium oxysporum f.sp. cubense (Foc), is one of important diseases in banana plant. Foc tropical race 4 (Foc4) is the most pathogenic race which could infect various banana cultivars including Cavendish cultivar which was previously considered as resistant cultivar. Molecular detection of Foc using PCR analysis is indispensable to determine the race of Foc. We demonstrate a faster DNA isolation procedure described in previous method by substituting sodium acetate precipitation with ammonium acetate precipitation without affecting the result. Based on our experience, some fungal genomes were troublesome to be amplified. We suggested pre-treatment step prior to amplification procedure by incubating fungal DNA in 65°C for 10 minutes for any samples of fungal genome, including stubborn samples, before mixing into PCR mix reagent. PCR reagents should be tested for stubborn samples since some of the reagents were unable to amplify the desired DNA fragment. Pre-treatment and the choice of robust PCR reagent should be taken into consideration for a reliable and consistent Foc4 molecular detection result.